Perceptions of Students and Teachers towards the Semester System of Tribhuvan University (Interdisciplinary Research in Education, 2019)
This paper intends to analyze perceptions of students and teachers towards the semester system of Tribhuvan University (TU). The result of the study is based on the data collected through survey questionnaire from 40 university teachers and 194 master level students. The perception is discussed in terms of learning environment, resources, use of ICT tools, contents and activities. The findings show that the perception of teachers and students towards curriculum, teaching/learning environment, and regularity of classes and viability of semester system are in positive direction. However, the availability of learning resources and use of ICT tools in day to day teaching/learning are not in satisfactory way in the perception of the participants. Their perceptions also reveal that facilities of extra-curricular activities, play grounds and canteen are inadequate. Similarly, the teachers and students perceive that availability of both human and academic resources is inadequate. The students experience show that there is teacher domination in selection of teaching methods; less use of ICT materials to promote learning; difficulty in completing courses in the stipulated time and not timely declaring exam result. However, this system has encouraged and empowered creativity among students for learning.